1996
DOI: 10.3354/meps132021
|View full text |Cite
|
Sign up to set email alerts
|

Response of herbivorous fishes to crown-of-thorns starfish Acanthaster planci outbreaks. II. Density and biomass of selected species of herbivorous fish and fish-habitat correlations

Abstract: Density, biomass and fish-habitat correlations were estimated for selected species of herbivorous fish on crown-of-thorns starfish (COTS) impacted and control reefs in the central Great Barrier Reef. The objective was to investigate a long-term numerical and/or biomass response to increased food availability (algal turfs) on COTS affected reefs. Out of 14 variates investigated, 2 showed evidence of a numerical response on COTS affected reefs. Importantly, total number of individuals and total biomass showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…They are commonly limited to single reefs or, at the most, to reef areas on a regional scale (e.g. Sano et al 1987, Hart et al 1996, Cheal et al 2002, Halford et al 2004). The 1997/1998 coral bleaching event was unique in that it affected coral reefs in all tropical seas and, hence, became the most extensive cause of coral mortality on record (Hoegh-Guldberg 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are commonly limited to single reefs or, at the most, to reef areas on a regional scale (e.g. Sano et al 1987, Hart et al 1996, Cheal et al 2002, Halford et al 2004). The 1997/1998 coral bleaching event was unique in that it affected coral reefs in all tropical seas and, hence, became the most extensive cause of coral mortality on record (Hoegh-Guldberg 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, coral mortality may have implications for herbivores as well, and, accordingly, they were primarily responsible for the recorded overall increase in fish abundance in the coral plots following coral death. Given their large home ranges (Hart et al 1996) and their rapid response to disturbance, as well as the limited size of our coral plots and their proximity to continuous reef, we believe that the observed increase in herbivores 6 mo after the bleaching was largely due to redistribution or increased feeding ranges. Hart et al (1996) suggested that roving herbivores should be able to benefit from sudden increases in turf algae, and a similar increase in herbivores was noted following an outbreak of Acanthaster planci (Wass 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive larval exchange between local populations will limit opportunities for local adaptation (Holt & Gaines 1992) and increase the evolutionary importance of phenotypically plastic traits (Warner 1997). If local populations in this region are largely open, then there are important implications that affect, for example: population regulation (Caley et al 1996;Armsworth 2002); the resiliency of reef fish communities to local disturbance (Wellington & Victor 1985;Russ 1991;Hart et al 1996;Roberts 1997); the spread of invading species (Randall & Kanayama 1972;Oda & Parrish 1982); and metapopulation growth rates, because of risk spreading and spatial averaging (Kuno 1981;Metz et al 1983;Bascompte et al 2002). However, the model predicts that a few local populations can be expected to consistently replenish themselves with larvae.…”
Section: Discussion (A) Model Predictionsmentioning
confidence: 99%
“…An increase in the abundance of some certain herbivorous fish species on degraded coral reefs has been described for bleached reefs by Lindahl et al (2001) and after experimental coral disturbance by Lewis (1998). In contrast, no change in the abundance and biomass of some herbivores was detected on reefs impacted by the crown-ofthorns starfish Acanthaster planci with subsequent algal overgrowth (Hart et al 1996).…”
Section: Human Impactmentioning
confidence: 93%